Variation of band edge, optical constant and dispersion parameters of CdS thin films due to disorder induced by fast neutron irradintion - Jabbar , Hashim (University of Thi-Qar Journal of Science, 2010)
CdS thin films were prepared by thermal evaporation method, optical constant of thedeposited films were obtained from the analysis of the expirmental recorded transmittancespectral data over a wavelength range of (200-900)nm. The value of refractive index ofunradiated and radiated samples are determined from these spectra using Swanepoel'smodel. It has been found that the dispersion data obey single-oscillator relation of the Wemple-DiDomenico model from which the dispersion parameters were determined the third order optical susceptibility χ(3) of unradiated and irradiated CdS thin film were alsodetermined using these spectra. and the optical absorption at the fundamental absorption edge was discussed. Direct optical energy gap   E opt g       and Urbach (localized states) energy  were also calculated for all unradiated and irradiated CdS thin films.